circITGA7 Functions as an Oncogene by Sponging miR-198 and Upregulating FGFR1 Expression in Thyroid Cancer - Li, Siqi (Biomed Res Int, 2020)
BACKGROUND: Emerging evidence has indicated that circular RNAs (circRNAs), recognized as functional noncoding transcripts in eukaryotic cells, may be involved in regulating many physiological or pathological processes. However, the regulation and function of circular RNA circITGA7 in thyroid cancer (TC) remains unknown. METHODS: In this study, we found that circITGA7 is upregulated in TC cell lines. We then performed functional analyses in the cell lines to support clinical findings. Mechanistically, we demonstrated that circITGA7 can directly bind to miR-198 and reduce the inhibition effect of miR-198 on target FGFR1 expression. RESULTS: We reported an upregulation of circITGA7 in patients with TC. Silencing of circITGA7 inhibits metastasis and proliferation of TC cell lines in vitro. In addition, in the TC cell lines, the knockdown of circITGA7 or overexpression of miR-198 significantly suppressed FGFR1 levels. Mechanistically, we found that circITGA7 acts as miR-198 competitive endogenous RNA (ceRNA) to regulate FGFR1 expression. CONCLUSIONS: In summary, circRNA circITGA7 may play a regulatory role in TC and may be a potential marker for TC diagnosis or progression.